2017
DOI: 10.14218/jcth.2016.00070
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Ledipasvir/Sofosbuvir with/without Ribavarin in Liver Transplant Recipients with Hepatitis C

Abstract: Background and Aims: Recurrent infection of hepatitis C virus (HCV) in liver transplant (LT) recipients is universal and associated with significant morbidity and mortality.Methods: We retrospectively evaluated the safety and efficacy of ledipasvir/sofosbuvir with and without ribavirin in LT recipients with recurrent genotype 1 hepatitis C.Results: Eighty-five LT recipients were treated for recurrent HCV with ledipasvir/sofosbuvirwith and without ribavirin for 12 or 24 weeks. The mean (± standard deviation [SD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Previous studies had focused on either the impact of RBV‐free treatment for 12 or 24 weeks or that of the duration of treatment post‐LT . We attempted to answer both questions: the need for RBV and the necessary duration of treatment for HCV recurrence in LT patients, by reporting on our real‐life experience of treating HCV recurrence with SOF and an NS5A inhibitor regimen in a large number of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies had focused on either the impact of RBV‐free treatment for 12 or 24 weeks or that of the duration of treatment post‐LT . We attempted to answer both questions: the need for RBV and the necessary duration of treatment for HCV recurrence in LT patients, by reporting on our real‐life experience of treating HCV recurrence with SOF and an NS5A inhibitor regimen in a large number of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Several sofosbuvir (SOF)‐based regimens have demonstrated their excellent efficacy and safety in treating post‐LT HCV recurrence. In particular, combining SOF with the nonstructural protein 5A (NS5A) inhibitors, ledipasvir (LDV) or daclatasvir (DCV), has shown remarkable efficacy post‐LT . The need for ribavirin (RBV) to achieve successful treatment post‐LT has also been studied .…”
mentioning
confidence: 99%
“…In patients with cirrhosis, the rates of SVR ranged from 94% to 100% in the four treatment groups[30]. Several other clinical and real-world studies and meta-analyses have also reported the efficacy of this regimen in treating HCV GT1-infected patients, including: (1) Both treatment naïve and treatment-experienced patients[31-49]; (2) Patients with compensated cirrhosis or advanced liver disease[31,36,38,40,44-46,48,50-52]; and (3) Liver transplantation cases (the transplantation cases studied included treatment-naïve as well as treatment-experienced and those with cirrhosis and HCC prior to transplantation)[50,53-59]. The presence of fibrosis, cirrhosis, or HCC has been found to lower the SVR rates with sofosbuvir and ledipasvir combination in HCV GT1-infected patients in a few studies[56,58-62].…”
Section: Optimizing the Management Of Hcv Infectionmentioning
confidence: 99%
“…Chronic hepatitis C virus (HCV) infection is the leading indication for liver transplantation (LT) in the United States . In 2013, the advent of all‐oral, interferon‐free direct‐acting antivirals (DAAs) transformed treatment options for HCV‐infected (HCV+) patients, and numerous studies have demonstrated the safety and efficacy of DAAs both pre‐ and post‐LT . With the approval of DAAs, providers were faced with the challenge of deciding whether to initiate treatment of HCV+ transplant candidates pre‐ or post‐LT.…”
Section: Introductionmentioning
confidence: 99%
“…treatment options for HCV-infected (HCV+) patients, and numerous studies have demonstrated the safety and efficacy of DAAs both pre-and post-LT. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] With the approval of DAAs, providers were faced with the challenge of deciding whether to initiate treatment of HCV+ transplant candidates pre-or post-LT. Weighing these options requires considering factors such as: a patient's disease severity and prognosis (as reflected in their model for end-stage liver disease…”
mentioning
confidence: 99%